Patient Satisfaction in Prescription Redemption at the Pharmacy Unit of X Hospital Surabaya - Wijaya, Hermanto; Geonarso, Roberto A (Journal of Health Management Research, 2023)
Background: One of the main services in hospitals are the pharmacy department. Pharmaceutical services are expected to be carried out according to established standards, to provide excellent service to patients. Aims: To determine the relationship between the quality of pharmaceutical services and patient satisfaction in the pharmaceutical installation of X Hospital Surabaya Methods: Quantitative research with cross sectional study design. The inclusion criteria in this study were patients/patients' families, aged 20-65 years, and willing to fill out a complete questionnaire. The independent variable is the quality of pharmaceutical services at X Hospital, the dependent variable is patient satisfaction at the X Hospital pharmacy installation. The study population was all patients both inpatient and outpatient at X Hospital, with a minimum sample size of 53 people. Results: Most of the respondents were female (60.38%), aged > 60 years (49.06%) with polyclinic visits mostly 3-4 times and most were college graduates (PT) (43.40%). There was a relationship between satisfaction of respondents with redemption process of drug prescriptions at the Pharmacy Unit of X Hospital Surabaya (p= 0.000 (α≤0.05) and r = 0.498). This shows that the respondents' expectations of the tangible, reliability, responsiveness, assurance and empathy components were well fulfilled. Satisfaction from several of these dimensions indicates a good match between the quality of service at the X Hospital Pharmacy Unit and the level of patient satisfaction. Conclusion: The quality of service at the Pharmacy Installation of X Hospital must be maintained and improved to provide satisfaction to the community. Accuracy in carrying out procedures and supported by the optimization of tangible components, reliability, responsiveness, assurance and empathy can certainly be a form of commitment in maintaining the quality of service in hospitals